BEBERAPA METODE PENGAMBILAN EKTOPARASIT PADA BURUNG MERPATI POS (COLUMBA LIVIA GMELEN) - AZIZ, JANITA; AMIR, M. (Research Center for Biology-Indonesian Institute of Sciences, 1988)
JANITA AZIZ & M. AMIR. 1988.Some ectoparasites collecting methods of racing pigeon (Columba livia Gmelin). Berita Biologi 3(8):382 - 385.Extraction of ectoparasites of living racing pigeons was done using modified